PENDEKATAN RESTORATIF DALAM PENYELESAIAN SENGKETA MEDIS: TINJAUAN LITERATUR - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
The restorative approach to medical dispute resolution presents an alternative to the traditional litigation system by emphasising relationship restoration and dialogic resolution. The main objective of this approach is to promote open communication and collaboration between patients, medical personnel, and other relevant parties in an effort to achieve a resolution that satisfies all parties involved. Through a literature review, this article analyses the basic principles and benefits of the restorative approach, such as increased empathy, trust, and reduced costs and time compared to formal litigation. On the other hand, this article also explores the challenges of implementation and the need for training and policy support to ensure the successful application of this method in the medical dispute resolution system.